2001
DOI: 10.1016/s0735-1097(01)01395-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting one-year mortality among elderly survivors of hospitalization for an acute myocardial infarction: results from the Cooperative Cardiovascular Project

Abstract: We demonstrate that a simple risk model can stratify older patients well by their risk of death one year after discharge for AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 15 publications
1
75
0
2
Order By: Relevance
“…3 In ENRICHD, prior to multivariable correction, a similar effect was observed. [5][6][7][8][9] After correction for confounders, the association disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In ENRICHD, prior to multivariable correction, a similar effect was observed. [5][6][7][8][9] After correction for confounders, the association disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Many studies have shown either no association or a favorable effect of obesity in patients with MI; others only a modest association with recurrent events. 1,[7][8][9][10] A pooled analysis of CAD patients has shown an inverse J curve with patients with BMI between 30-35 having the lowest long-term mortality. 11 Weight change after MI could affect the disease trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…For EF, an indicator variable reflecting missing values was included in models analyzing the incremental contribution of EF over the scores. 7 Ancillary analyses compared this approach to the complete case analysis and to imputation.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, the scores have not been directly compared with one another in the same population, which is important for determining their respective value. Finally, although the Cooperative Cardiovascular Project score 7 underscored the prognostic value of the ejection fraction (EF) after MI, most scores do not include it. Thus, it is unknown whether adding the EF to these scores would increase their predictive power.…”
mentioning
confidence: 99%
See 1 more Smart Citation